Public Health Student's Attitudes Toward Research - Chand, Benjamin R.; Eio, Crystal; Alysandratos, Annastasia; Thompson, Jake; Ha, Tam (Frontiers in Public Health, 2022)
Research is able to improve the lives of big populations by investigating effective interventions and then implementing those through public health policies. Whilst research on the inclination of Medical or Science undergraduate and postgraduate students has been conducted, little is known about what students pursuing a Masters degree in Public Health perceive the purpose of research to be. Their perceptions and inclinations will shape their research pursuits and career directions, which impacts the health outcomes of the community. Our findings suggest MPH students see improving the lives of the community as the most important purpose of research. Student's had more inclination to pursue research when influenced by a mentor however, many students still claimed that they either lacked confidence and skills in completing research or had no intention of pursuing research beyond their degrees, which suggests the need for curriculum adjustments.